2020
DOI: 10.3847/1538-4357/ab7b64
|View full text |Cite
|
Sign up to set email alerts
|

When Does the Onset of Multiple Stellar Populations in Star Clusters Occur? III. No Evidence of Significant Chemical Variations in Main-sequence Stars of NGC 419

Abstract: Recent studies have revealed that the onset age for the presence of multiple stellar populations (MPs) in star clusters seems to correspond to the disappearance of the extended main-sequence turnoff (eMSTO) in young clusters, a pattern associated with stellar rotations. A speculative suggestion is that MPs might be caused by the magnetic brake, a stellar evolutionary effect linked to the rotation. In this work, we use the young massive cluster NGC 419 as a testbed. We examined if its magnetically baked MS star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…We note thatLi et al (2020) came to similar conclusions with the same data set in a paper that appeared after the submission of this paper. In summary, they fitted synthetic clusters with different degrees of N abundance variations to the observations of low-mass MS stars of NGC 419.…”
supporting
confidence: 74%
“…We note thatLi et al (2020) came to similar conclusions with the same data set in a paper that appeared after the submission of this paper. In summary, they fitted synthetic clusters with different degrees of N abundance variations to the observations of low-mass MS stars of NGC 419.…”
supporting
confidence: 74%
“…However, NGC 419 (e.g. Martocchia et al 2017;Li et al 2020), NGC 1806 (Mucciarelli et al 2014) and NGC 1783 (Zhang et al 2018) were found to be consistent with SSPs clusters. The fact that these clusters likely had similar initial masses and that MPs have not been found in young massive clusters (YMCs) (Cabrera-Ziri et al 2016), led several authors to argue that cluster age may also be an indicator of the presence of MPs within clusters and that only clusters older than ∼ 2 Gyr show evidences of MPs (Li & de Grijs 2019;Martocchia et al 2019Martocchia et al , 2021.…”
Section: Global Parameters and The Onset Of Mpsmentioning
confidence: 85%
“…However, this conclusion is also challenged by e.g. NGC 419 (Li et al 2020) which is a massive cluster but with no apparent signs of MSPs.…”
Section: Introductionmentioning
confidence: 99%